Lời giải:
ĐKXĐ:........
Bình phương 2 vế ta có:
\(\Rightarrow x+(9-x)+2\sqrt{x(9-x)}=-x^2+9x+9\)
\(\Leftrightarrow 2\sqrt{x(9-x)}=-x^2+9x=x(9-x)\)
\(\Leftrightarrow \sqrt{x(9-x)}(2-\sqrt{x(9-x)})=0\)
\(\Rightarrow \left[\begin{matrix} \sqrt{x}=0(1)\\ \sqrt{9-x}=0(2)\\ 2=\sqrt{x(9-x)}(3)\end{matrix}\right.\)
Với \((1)\Rightarrow x=0\) (t/m)
Với (2)\(\Rightarrow x=9\) (t/m)
Với (3): \(\Rightarrow 4=x(9-x)\)
\(\Leftrightarrow x^2-9x+4=0\)
\(x=\frac{9\pm \sqrt{65}}{2}\) (đều thỏa mãn)
Vậy............